PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KOMPETENSI PENGETAHUAN DAN KETRAMPILAN BERPIKIR KRITIS SISWA MADRASAH ALIYAH BPD IHA TENTANG KONFLIK - Hallatu, Yosepus; Prasetyo, Ketut; Haidar, Ali (Jurnal Penelitian Pendidikan, 2017)
This study aimed is to determine the effect of problem based learning model of the competence of knowledge and critical thinking skills of students about the conflict between the villages. This study  uses experimental research design.  The techniques of pretest-posttest randomized  control  design is used in this study. The  population was the whole of the class XI at Madrasah Aliyah BPD (board of villages organizer )  Iha  in Maluku Province which consists of three classes. While the  sample consisted of two classes, namely XI 2 as an experimental class that implements the model problem based learning and XI 3 as the control class that implements direct instructional model. The t-test  is used to analize the data .  The results showed that the descriptive analysis model of problem based learning effect to enhance the competence of knowledge and critical thinking skills of students based on several things, namely: (1) the  students activity is categorized  actif, (2) completeness of the learning outcomes achieved. This is indicated by sig 0,000 ≤ 0.05 and the t calculated  (5.637) ≥ t table (1.688). This means that there are differences in the average post-test students on the model of problem based learning is better than direct learning model in terms of improving the knowledge and competence of critical thinking skills.